He raised the name of His Majesty (Allah) in His saying, the Most High:  If there were no gods in them but Allah, they would have been corrupted  [The Prophets] 22 (Journal of the College of Basic Education, 2023)
Grammar is a noble and complex science, especially in the topics of the Holy Qur’an. Because his provisions are subjectFor significance first, for high literary taste secondly, for context thirdly, and without influences, and he must be blamed for this.Scholars, especially those specialized in linguistics and interpretation of the Qur’an and all its sciences, and in the noble hadith, evenOther types of sciences. What is mentioned about Sibawayh (d. 180 AH) approaching him, and his proficiency inThe majesty of this science, the greatness of its value, its danger, and the necessity of mastering it from scholars who specialized in other than the linguistic sciences.As it is narrated from him that he was specialized in noble hadith and jurisprudence (and he was a follower of Hammad bin Maslamah, and he wasHammad is eloquent, so he learned it one day from the words of the Messenger of God (may God bless him and his family and grant them peace): (He is not one of my companions.He is not Abu Al-Darda') He said: Sibawayh: Not Abu Al-Darda', so he shouted at himHammad: I sang, O Sibawayh, this is not what I went, but it is an exception.Do not compel me with him.grammarians) (1). Then what was written by him (the book) was what made you realize what the book was?!The same applies to guiding the semantics of the Qur’anic text, especially in what was confusing to linguists.And the interpretation of it, so they perverted the meanings, and tolerated the interpretation, so they changed the grammatical limits, orIn Arabic, for example, in the words of the Most High:  They said, “O our father, why should this be ours? It has been returned to us.”[Yusuf.] 65: By confirming the (yaa) in (we should), and by omitting it in the Almighty’s saying:  He said that we would not  [Al-Kahf][64: Or the affirmation of the present tense with the noun of affirmation, despite the fact that it is negative, contrary to what the grammar scholars have established.One of the rules of affirmation is the present tense with nouns of affirmation, as in the Almighty’s saying:Enter your dwellings, lest any of you be destroyed by Sulayman and his soldiers (2)  [An-Naml 18:]In the blessed verse in which the research is conducted, which is the Almighty’s saying:  If there were no gods in them but Allah, they would certainly have been corrupted